FACTORS DETERMINING ACCEPTANCE LEVEL OF INTERNET BANKING IMPLEMENTATION - Mahardika Aditya Widjana (Universitas Hayam Wuruk Perbanas, 2011)
The purpose of this research is to determine the factors influencing acceptance level of inter- net banking by the bank customers in Surabaya. There are ten constructs compiled into a structural model to explain the customer acceptance level of internet banking, i.e. awareness of service, security, quality of internet connection, computer self efficacy, perceived useful- ness, perceived ease of use, perceived enjoyment, trust, attitude towards using, and adoption intention. The data were collected using convenience sampling method by randomly taking all the bank customers that have used internet banking in Surabaya. Only 193 questionnaires were taken and analyzed because due to some circumstances. The method of analysis is by means of partial least square (PLS) using the program of SmartPLS 2.0. The results show that the overall proposed hypotheses are accepted except two hypotheses relationship be- tween awareness of service to the perceived usefulness and security to the perceived useful- ness are considered to have no significant relationship. The management implication and suggestions for the banks as internet banking service providers are also discussed.